2020
DOI: 10.1016/j.bbih.2020.100138
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous vagal nerve stimulation blocks stress-induced activation of Interleukin-6 and interferon-γ in posttraumatic stress disorder: A double-blind, randomized, sham-controlled trial

Abstract: Posttraumatic stress disorder (PTSD) is a highly disabling condition associated with alterations in multiple neurobiological systems, including increases in inflammatory function. Vagus nerve stimulation (VNS) decreases inflammation, however few studies have examined the effects of non-invasive VNS on physiology in human subjects, and no studies in patients with PTSD. The purpose of this study was to assess the effects of transcutaneous cervical VNS (tcVNS) on inflammatory responses to stress. Thirty subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 183 publications
1
17
0
Order By: Relevance
“…Recent work has shown that effects of auricular stimulation on cardiac function do not outlast the stimulation epoch [61]. The short-duration (<1 s), discrete pulse trains used in the present study are less likely to elicit carryover effects observed with continuous, 2-min bouts of stimulation used in previous studies examining inflammatory and neuropeptide responses [62,63]. To minimize the potential for carryover, 10 min elapsed between sets of trials at each stimulation frequency; location and frequency conditions were also counterbalanced.…”
Section: Eye Tracking Configurationmentioning
confidence: 56%
“…Recent work has shown that effects of auricular stimulation on cardiac function do not outlast the stimulation epoch [61]. The short-duration (<1 s), discrete pulse trains used in the present study are less likely to elicit carryover effects observed with continuous, 2-min bouts of stimulation used in previous studies examining inflammatory and neuropeptide responses [62,63]. To minimize the potential for carryover, 10 min elapsed between sets of trials at each stimulation frequency; location and frequency conditions were also counterbalanced.…”
Section: Eye Tracking Configurationmentioning
confidence: 56%
“…Research into MDMA-assisted psychotherapy, as well as other nontraditional treatment options for PTSD (e.g., vagal nerve stimulation, stellate ganglion blockade), has occurred because of the non-response rates that were observed with traditional therapies [ 35 ]. While CBT with prolonged exposure therapy is effective in some patients, it takes time and considerable expertise [ 36 ], and the efficacy of SSRIs in the treatment of PTSD has recently come into question [ 37 , 38 ]. Furthermore, less than half of patients with PTSD either seek or receive treatment, and for those that do, the dropout rate is approximately 24% [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…While CBT with prolonged exposure therapy is effective in some patients, it takes time and considerable expertise [ 36 ], and the efficacy of SSRIs in the treatment of PTSD has recently come into question [ 37 , 38 ]. Furthermore, less than half of patients with PTSD either seek or receive treatment, and for those that do, the dropout rate is approximately 24% [ 36 ]. Feduccia et al [ 32 ] compared data that was used for the approval of the only two FDA-approved oral medications for the treatment of PTSD, sertraline and paroxetine, with the data for MDMA-assisted psychotherapy that was submitted for its successful breakthrough therapy application.…”
Section: Reviewmentioning
confidence: 99%
“…VNS can be applied to branches of the vagus nerve in the ear (transcutaneous auricular VNS, or taVNS) or in the neck, where it travels through the carotid sheath (transcutaneous cervical VNS, or tcVNS) ( Adair et al, 2020 ; Badran et al, 2019 ; Bremner et al, 2020b ). PTSD is associated with an increase in the blood concentrations of the inflammatory marker interleukin (IL)-6 at baseline ( Gill et al, 2010 ; Gill et al, 2008 ; ( Guo et al, 2012 ); Li et al, 2014 ; Lindqvist et al, 2017 ; Miller et al, 2001 ; Passos et al, 2015 ; Sutherland et al, 2003 ; Tucker et al, 2010 ; Vidovic et al, 2011 ; von Kanel et al, 2010 ) and in response to mental stress such as public speaking ( Lima et al, 2019 ) or exposure to personalized traumatic scripts ( Bremner et al, 2020a ) as well as in diurnal cerebrospinal fluid (CSF) ( Baker et al, 2001 ). Studies have shown increased blood concentrations of interferonγ (IFNγ) at baseline ( Guo et al, 2012 ; Hoge et al, 2009 ; Lindqvist et al, 2014 ; Passos et al, 2015 ; Woods et al, 2005 ; Zhou et al, 2014 ) and in response to traumatic script stress in PTSD ( Bremner et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…PTSD is associated with an increase in the blood concentrations of the inflammatory marker interleukin (IL)-6 at baseline ( Gill et al, 2010 ; Gill et al, 2008 ; ( Guo et al, 2012 ); Li et al, 2014 ; Lindqvist et al, 2017 ; Miller et al, 2001 ; Passos et al, 2015 ; Sutherland et al, 2003 ; Tucker et al, 2010 ; Vidovic et al, 2011 ; von Kanel et al, 2010 ) and in response to mental stress such as public speaking ( Lima et al, 2019 ) or exposure to personalized traumatic scripts ( Bremner et al, 2020a ) as well as in diurnal cerebrospinal fluid (CSF) ( Baker et al, 2001 ). Studies have shown increased blood concentrations of interferonγ (IFNγ) at baseline ( Guo et al, 2012 ; Hoge et al, 2009 ; Lindqvist et al, 2014 ; Passos et al, 2015 ; Woods et al, 2005 ; Zhou et al, 2014 ) and in response to traumatic script stress in PTSD ( Bremner et al, 2020a ). Other studies showed increased baseline Tumor Necrosis Factor (TNF)-α blood concentrations in PTSD ( Gill et al, 2010 ; Lindqvist et al, 2017 ; Lindqvist et al, 2014 ; Passos et al, 2015 ; Sutherland et al, 2003 ; Vidovic et al, 2011 ; von Känel et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%